2018
DOI: 10.1186/s12917-018-1343-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease (IBD) in horses: a retrospective study exploring the value of different diagnostic approaches

Abstract: BackgroundDiagnosing IBD in horses is challenging and requires a multimodal approach, since no conclusive diagnostic test is available.The objectives of this study were to provide an overview of population characteristics, results of applied diagnostic tests, treatment modalities and outcome in a large group of horses thought to have IBD and that were presented to four large equine referral hospitals, and to provide an exploratory investigation of possible associations between results of applied diagnostic tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(70 citation statements)
references
References 29 publications
(57 reference statements)
4
60
1
4
Order By: Relevance
“…10 € je Probe teurer als die Bestimmung der Blutglukosekonzentration. [45]. Die vorherige Gabe von n-Butylscopolamin (Buscopan ® comp.)…”
Section: Intestinales Mikrobiom: Klein Aber Ohounclassified
“…10 € je Probe teurer als die Bestimmung der Blutglukosekonzentration. [45]. Die vorherige Gabe von n-Butylscopolamin (Buscopan ® comp.)…”
Section: Intestinales Mikrobiom: Klein Aber Ohounclassified
“…Similarly, Boshuizen et al 15 reported weight loss as the most common clinical sign associated with IBD and over 70 per cent of horses thought to have IBD had an abnormal OGTT. All horses included in the current paper presented with weight loss as the main clinical sign.…”
Section: Discussionmentioning
confidence: 92%
“…The clinical symptoms and molecular features have been found to be common in both animals and humans [198][199][200][201][202][203] ; however, some animal breeds are more predisposed to IBD. 199,201,[204][205][206][207][208] There is speculation that IBD evolved partially due to an inappropriate immune response to bacterial and/or dietary antigens. Food sensitivities and allergies contribute to compromised immune function.…”
Section: Veterinary Medicine Translational Medicine and Medical Canmentioning
confidence: 99%